2006
DOI: 10.1143/jpsj.75.043708
|View full text |Cite
|
Sign up to set email alerts
|

Magic Angle Effects of One-Dimensional Axis Conductivity in Quasi-One-Dimensional Conductors

Abstract: In quasi-one-dimensional conductors, the conductivity in both one-dimensional axis and interchain direction shows peaks when magnetic field is tilted at the magic angles in the plane perpendicular to the conducting chain. Although there are several theoretical studies to explain the magic angle effect, no satisfactory explanation, especially for the one-dimensional conductivity, has been obtained. We present a new theory of the magic angle effect in the one-dimensional conductivity by taking account of the mom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, these peaks are not large enough to explain the observed peaks [1,2]. The electron correlation is expected to play an important role in the magic angle effect in s xx as we have considered previously [6,7]. (10) is limited to À5om; no5.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…However, these peaks are not large enough to explain the observed peaks [1,2]. The electron correlation is expected to play an important role in the magic angle effect in s xx as we have considered previously [6,7]. (10) is limited to À5om; no5.…”
Section: Resultsmentioning
confidence: 83%
“…We have shown the large peaks in s xx in a simple model [6]. We have also shown that in the random phase approximation the relative height of each peaks is changed by t and v x which depend on k y and k z due to electron interaction [7].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…8 It is found that the angle dependence of 1D axis magnetoconductivity (σ xx ) appears when a spot of slow or fast velocity exists in the momentum space of the 1D axis velocity. 9 The result in this simple model indicates the possibility that the change in velocity near SDW causes the strong angle dependence in σ xx .…”
mentioning
confidence: 75%